Assessing Local Government Responsibility in Protecting Traditional Fishermen through Fisheries Insurance - Bimantara, Gesa; Labibah, Hanin Alya’; Tina, Neli Agus (Jurnal Ilmu Hukum Kyadiren, 2026)
Traditional fishermen constitute a category of workers exposed to a high level of occupational safety risk, yet they have not received adequate and effective legal protection. One of the policy instruments developed by the state to safeguard fishermen is the fisheries insurance scheme. This study examines the responsibility of local governments in providing legal protection for traditional fishermen through the implementation of fisheries insurance, with a particular focus on Tuban Regency. The research employs an empirical legal method using a socio-legal approach. Data were collected through interviews with local government officials and traditional fishermen, complemented by an analysis of relevant laws and regulations and a review of the existing literature. The findings indicate that although fisheries insurance is supported by a sufficient legal framework, it has not yet functioned as substantive legal protection in practice. Its implementation remains largely administrative, while legal education and assistance with insurance claims are inadequately provided, resulting in legal protection that falls short of delivering legal certainty, tangible benefits, and a sense of security for fishermen.